Mapping the Functions and Contributions of Applied Linguistics in Higher Education: Insights from Contemporary Research - Hamuddin, Budianto; Ningrum, Fatma Setya; Meutya Rizky Ramadhani (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study addresses the critical gap in understanding the evolving roles and functions of applied linguistics (AL) within higher education, particularly its impact on multilingual education, curriculum development, and institutional policies. Using a systematic literature review approach, 24 studies were selected from an initial pool of 2,189, focusing on AL's applications in higher education contexts. The review reveals significant contributions of AL, including innovative teaching methodologies like translanguaging, the integration of technology in language education, and the formulation of inclusive language policies. However, challenges persist, such as the scalability of technology in low-resource environments and the limited empirical validation of multilingual strategies. These findings underscore the need for adaptive educational frameworks that align linguistic theories with practical outcomes. By bridging theoretical insights with real-world applications, this study advocates for AL as a tool to enhance teaching quality, promote linguistic diversity, and address educational inequities. The implications extend beyond academia, offering policymakers and educators actionable strategies to create inclusive and sustainable educational paradigms that reflect the complexities of a globalized academic environment. This research contributes to the broader discourse on fostering equitable, context-sensitive, and innovative approaches in higher education, positioning AL as a cornerstone for addressing contemporary linguistic and pedagogical challenges.